2017
DOI: 10.3390/molecules22081333
|View full text |Cite
|
Sign up to set email alerts
|

Readily Available Chiral Benzimidazoles-Derived Guanidines as Organocatalysts in the Asymmetric α-Amination of 1,3-Dicarbonyl Compounds

Abstract: The synthesis and the evaluation as organocatalysts of new chiral guanidines derived from benzimidazoles in the enantioselective α-amination of 1,3-dicarbonyl compounds using di-t-butylazodicarboxylate as aminating agent is herein disclosed. The catalysts are readily synthesized through the reaction of 2-chlorobezimidazole and a chiral amine in moderate-to-good yields. Among all of them, those derived from (R)-1-phenylethan-1-amine (1) and (S)-1-(2-naphthyl)ethan-1-amine (3) turned out to be the most efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In the last years, our research group has been involved in the synthesis and application of benzimidazole derivatives as bifunctional organocatalysts which activate different active methylene compounds through hydrogen bond interactions in different asymmetric organocatalyzed transformations [ 15 , 16 , 17 , 18 , 19 ]. More concretely, a few years ago we reported the successful employment of such organocatalysts in the enantioselective electrophilic amination of 1,3-dicarbonyl compounds [ 20 , 21 ]. Continuing with this research line, we disclose the application of 2-aminobenzimidazoles as catalysts in the asymmetric electrophilic amination of 3-substituted unprotected oxindoles ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, our research group has been involved in the synthesis and application of benzimidazole derivatives as bifunctional organocatalysts which activate different active methylene compounds through hydrogen bond interactions in different asymmetric organocatalyzed transformations [ 15 , 16 , 17 , 18 , 19 ]. More concretely, a few years ago we reported the successful employment of such organocatalysts in the enantioselective electrophilic amination of 1,3-dicarbonyl compounds [ 20 , 21 ]. Continuing with this research line, we disclose the application of 2-aminobenzimidazoles as catalysts in the asymmetric electrophilic amination of 3-substituted unprotected oxindoles ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has established the practicality of bifunctional chiral 2-aminobenzimidazole derivatives [20,21] 1 and 3 (Scheme 1) as efficient organocatalysts in the asymmetric conjugate addition of 1,3-dicarbonyl compounds to nitroolefins [22] and maleimides [23,24] as well as in the αfunctionalization [25][26][27][28] of these interesting nucleophiles using volatile organic solvents (VOCs) as a reaction medium. More fascinating, we have also demonstrated that the catalytic system based on the deep eutectic solvent choline chloride/glycerol and chiral 2-aminobenzimidazole organocatalysts 2 efficiently promotes the enantioselective addition of 1,3-dicarbonyl compounds to β-nitrostyrenes, avoiding the use of toxic VOC as reaction media [29].…”
Section: Introductionmentioning
confidence: 99%